Ullmann's Encyclopedia of Industrial Chemistry 2012
DOI: 10.1002/14356007.a07_197.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Coal Liquefaction

Abstract: The article contains sections titled: 1. Introduction 1.1. Commercial Development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 284 publications
0
27
0
2
Order By: Relevance
“…Thed eoxygenation of epoxides to the corresponding alkenes under WGSR conditions has been known since 1968, when Watanabe et al reported the reduction of styrene oxide with K 2 Fe(CO) 4 . [140] However, the development of synthetically useful reduction protocols occurred only in the last decade with the advent of nanoparticle catalysts.H ydrotalcite-supported silver [141] and gold, [142] as well as titaniasupported gold nanoparticles, [143] are efficient promoters of the reduction of av ariety of epoxides ( Figure 11).…”
Section: Deoxygenation Of Epoxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thed eoxygenation of epoxides to the corresponding alkenes under WGSR conditions has been known since 1968, when Watanabe et al reported the reduction of styrene oxide with K 2 Fe(CO) 4 . [140] However, the development of synthetically useful reduction protocols occurred only in the last decade with the advent of nanoparticle catalysts.H ydrotalcite-supported silver [141] and gold, [142] as well as titaniasupported gold nanoparticles, [143] are efficient promoters of the reduction of av ariety of epoxides ( Figure 11).…”
Section: Deoxygenation Of Epoxidesmentioning
confidence: 99%
“…Also, it is used to tune the H 2 /CO ratio in the production of methanol [3] and in the Fischer–Tropsch process for the synthesis of hydrocarbons. [4] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the Fischer – Tropsch process for producing hydrocarbons and the production of methanol from synthesis gas are industrial applications of the WGSR. 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…Außerdem wird die WGSR zur Einstellung des H 2 /CO-Verhältnisses in der Methanolherstellung [3] und in der Fischer-Tropsch-Synthese von Kohlenwasserstoffen genutzt. [4] Die WGSR ist nicht auf industrielle Anwendungen beschränkt, vereinzelt wurde sie auch in der organischen Synthese als Methode zur Durchführung reduktiver Prozesse genutzt. Hierbei ist H 2 kein direktes Produkt der Reaktion, vielmehr wird das reduktive Potenzial der WGSR auf die Reduktion der organischen Substrate gelenkt oder zur Gewährleistung des Umsatzes der Katalysezyklen genutzt.…”
Section: Introductionunclassified